Electrodeposition of zinc and nickel to improve standard industrial galvanizing - Villon, Angel Eduardo (2021)
An improved galvanizing with the Zn and Ni co-deposition, achieved an improvement in the hardness at 140-148 HV and a corrosion rate of 4.8-6.4 mpy with a deposit of 9.8% Ni and 90.2% of Zn, with a salt bath of Ni and Zn sulphate at pH 1-3, using as additives thiourea, sodium gluconate and boric acid among others, with differentiated current densities for each anode, nickel with 6 A/dm2 and for zinc 5 A/dm2, the times used were enough to cause an adequate thickness for tests of 10-15 minutes, with an electrolytic cell with agitation, with cathodic efficiency of 48 to 65%.